Nutrient analysis of sand-laden dairy manure - T. Strahm; Joseph P. Harner; David V. Key; James P. Murphy (Kansas Agricultural Experiment Station Research Reports, 1999)
Nine concrete storage basins were sampled on Kansas dairies and analyzed for nutrient content of sand-laden dairy manure. The manure average 75% moisture content during the three sampling periods. The average total nitrogen, phosphate, and potash were 9.7, 4.6, and 7.4 lb/ton, respectively. The data collected from the basin indicated that when the scraped manure from a dairy is applied at an agronomic rate of 15 tons or less per acre, accumulation of nutrients should be minimal, in particular phosphorus. The manure value was $3 to $4 per ton depending on whether commercial sources of phosphorus normally would be applied to the cropland.; Dairy Day, 1999, Kansas State University, Manhattan, KS, 1999;
Keywords: Dairy Day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-136-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 842; Dairy; Manure; Nutrients; Sand